Improving the resilience of small-scale food entrepreneurs in the new norm through government assistance during Covid-19 pandemic era - Harifah Mohd Noor; Rima Abdul Rahman; Ubong Imang; Adilah Md. Ramli; Tatas Hardo Brotosudarmo (e-International Publishing House, Ltd., 2022)
The presence of small-scale food enterprises contributes significantly to the country's income while also providing numerous job opportunities in the community. The purpose of this study was to look at how small-scale food entrepreneurs try to stay in business while dealing with the effects of COVID-19. The resilience factor was developed using factor analysis, and descriptive analysis was used to examine demography, resilience practices, and the assistance in improving entrepreneurial resilience. This research has identified three resilience factors: add skills, new strategies, and reduce expenses. However, entrepreneurs must improve their resilience by utilizing government assistance. As a result, the government must be vigilant in providing entrepreneurs with the assistance they require to rehabilitate businesses affected by the COVID-19 pandemic.